Stabilitas Ekonomi dan Pengumpulan Zakat: Studi pada Enam BAZNAS Provinsi di Indonesia - Lidyana Arifah (ZAWA: Management of Zakat and Waqf Journal, 2024)
This research examines the influence of macroeconomic variables, namely inflation, economic growth and unemployment rate on zakat collection in five BAZNAS provinces in Indonesia. Using panel data analysis for 8 years from 2016-2023. This research explores the extent to which economic factors influence zakat collection. The research results show that inflation and economic growth do not significantly influence zakat collection, which indicates that zakat contributions are relatively stable despite changes in these two variables. However, the unemployment rate has a significant negative influence which shows that an increase in the unemployment rate is correlated with fluctuations in zakat collection. These findings emphasize the importance of decreasing the unemployment rate as a key factor in optimizing the zakat collection system and ensuring the sustainability of zakat as a social and economic instrument.